Demand Response in Smart Grids - Faria, Pedro; Vale, Zita (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Demand Response in Smart Grids" includes 11 papers on a variety of topics. The success of this Special Issue demonstrates the relevance of demand response programs and events in the operation of power and energy systems at both the distribution level and at the wide power system level. This reprint addresses the design, implementation, and operation of demand response programs, with focus on methods and techniques to achieve an optimized operation as well as on the electricity consumer.